2019
DOI: 10.3389/fphar.2019.01096
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects and Mechanisms of Zhenlong Xingnao Capsule in In Vivo and In Vitro Models of Hypoxia

Abstract: Zhenlong Xingnao Capsule (ZXC) is a Tibetan medicine used to treat ischemic stroke. In this study, we determined the in vitro and in vivo effects of ZXC on reactive oxygen species (ROS) in a mouse BV-2 microglial cell hypoxia-reoxygenation and rat middle cerebral artery occlusion infarction models. We aimed to clarify the role of ZXC in cerebral ischemia protection; reveal amino acid neurotransmitter changes in the frontal cortex after drug intervention; determine mRNA and protein expression changes in Bcl-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…T‐SOD is a key player in preserving body's oxidative and antioxidant equilibrium by destroying superoxide radicals. Its activity is a metaphor for organism's capacity to scavenge oxygen free radicals 42 . GSH‐Px scavenges ROS and hydroxyl radicals by catalyzing glutathione oxidation, shielding organisms from environmental stress 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T‐SOD is a key player in preserving body's oxidative and antioxidant equilibrium by destroying superoxide radicals. Its activity is a metaphor for organism's capacity to scavenge oxygen free radicals 42 . GSH‐Px scavenges ROS and hydroxyl radicals by catalyzing glutathione oxidation, shielding organisms from environmental stress 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Its activity is a metaphor for organism's capacity to scavenge oxygen free radicals. 42 GSH-Px scavenges ROS and hydroxyl radicals by catalyzing glutathione oxidation, shielding organisms from environmental stress. 43 CAT disintegrates hydroxyl radicals and breaks down hydrogen superoxide into water, and then water interacts with peroxidase to create an extreme efficient antioxidant reaction chain.…”
Section: Discussionmentioning
confidence: 99%
“…However, factors such as delayed patient presentation for medical care have contributed to the low utilization rate of thrombolytic treatment for acute ischemic stroke (3). Studies have demonstrated that hypoxia/ reoxygenation can lead to cerebral injury through various mechanisms, resulting in phenomena like cellular apoptosis, neuronal demise, and microglial cell activation (4,5). Consequently, the development of innovative therapeutic strategies targeting neurodegenerative diseases induced by hypoxia/reoxygenation is of significant importance.…”
Section: Introductionmentioning
confidence: 99%